Volume 3: Coal, Biomass and Alternative Fuels; Combustion and Fuels; Oil and Gas Applications; Cycle Innovations 1987
DOI: 10.1115/87-gt-139
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of the Design of Swirlers as Used in Fuel Injectors for Gas Turbine Combustors

Abstract: An attempt is made to review the state of the art, in swirler design and performance, as it applies to airblast atomizers. The purpose of this review is to summarize existing information on swirler design aspects and performance, as well as to clarify and initiate the standardization of terminology relating to swirlers and swirling flow.First, a brief, general discussion is presented on characteristics of swirling flows. Next, the more common methods of swirl production arc described, followed by a more specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Swirlers appear to be disarmingly simple, but like most things they have a complexity and technology of their own. The helical swirlers studied here show the linearity of thrust, and torque versus pressure drop plus the swirl number independence of it noted by Martin (4). Furthermore, the data suggests that there may be an optimum configuration with relative maximum effective area and near maximum of swirl number occurring at about a vane angle of 40°.…”
Section: Closuresupporting
confidence: 66%
See 2 more Smart Citations
“…Swirlers appear to be disarmingly simple, but like most things they have a complexity and technology of their own. The helical swirlers studied here show the linearity of thrust, and torque versus pressure drop plus the swirl number independence of it noted by Martin (4). Furthermore, the data suggests that there may be an optimum configuration with relative maximum effective area and near maximum of swirl number occurring at about a vane angle of 40°.…”
Section: Closuresupporting
confidence: 66%
“…In a recent paper Martin (4) indicates that for an axial swirler, swirl torque and thrust are linear functions of pressure drop through the swirler, while their ratio, "swirl number", is independent of pressure drops L P>5 in 1120 (0. vanes is a function of the gap to chord ratio, S/c, (5). Modifying this to be also a function of vane angle and inverting it, the following solidity relation is obtained.…”
Section: Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Radius R C describes the core radius of the swirl generator and R Z the cyclones inner radius. To improve inflow conditions, the transition region is defined with h E = 0.015 m, guaranteeing lower pressure losses Δ p in comparison to sharp‐angled baffles . α SVI represents the outer vane angle of the blades at radius R Z .…”
Section: Methodsmentioning
confidence: 99%
“…Keshtkar [43] demonstrated that the variation of vane angle can affect the size of the flame and decrease the pollutants generated during combustion. These swirler vanes can be designed with two shape types: flat or curved [44]. Thus, Beer and Syred [45] evaluated the performance of curved and flat vanes of swirlers.…”
Section: Designmentioning
confidence: 99%